2013
DOI: 10.1007/s00223-013-9716-8
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular and Cortical Microarchitecture in Postmenopausal HIV-Infected Women

Abstract: Objective To assess the effects of HIV infection and antiretroviral therapy (ART) on trabecular and cortical microarchitecture in postmenopausal minority women. Methods A subgroup of 106 (46 HIV-infected, 60 uninfected) postmenopausal Hispanic and African American women from an established cohort had areal bone mineral density (aBMD) measured by dual-energy x-ray absorptiometry, and trabecular and cortical volumetric BMD (vBMD) and microarchitecture measured by high-resolution peripheral quantitative compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
(45 reference statements)
1
23
0
1
Order By: Relevance
“…Biver et al (10) found trabecular bone microstructure alterations with lower Tb.N and higher Tb.Sp at the distal radius, as well as lower DXA aBMD at the total femur and ultra-distal radius, in HIVinfected men (median age =64 years) compared to healthy age-, BMI-, and gender-matched controls. In contrast, Yin et al (11) did not find significant differences in structural HR-pQCT parameters of trabecular bone at the distal radius and distal tibia between HIV-infected women (mean age =58 years) and uninfected controls, but found lower DXA aBMD at the spine, total hip and ultradistal radius in HIV-infected women.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Biver et al (10) found trabecular bone microstructure alterations with lower Tb.N and higher Tb.Sp at the distal radius, as well as lower DXA aBMD at the total femur and ultra-distal radius, in HIVinfected men (median age =64 years) compared to healthy age-, BMI-, and gender-matched controls. In contrast, Yin et al (11) did not find significant differences in structural HR-pQCT parameters of trabecular bone at the distal radius and distal tibia between HIV-infected women (mean age =58 years) and uninfected controls, but found lower DXA aBMD at the spine, total hip and ultradistal radius in HIV-infected women.…”
Section: Discussionmentioning
confidence: 78%
“…To the best of our knowledge, only two published studies have investigated bone quality in older HIV-infected individuals (10,11). However, these studies investigated bone quality only at the extremities using HR-pQCT and reported conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRpQCT allows for 3-dimensional assessment of bone macro- and microarchitecture (e.g., cortical porosity and trabecular connectivity) of the distal radius and tibia. This technology has showed increased cortical porosity in post-menopausal women [66], patients with type 2 diabetes mellitus [67], and with HIV-1 infection [68]. …”
Section: Introductionmentioning
confidence: 99%
“…In 46 HIV-positive postmenopausal women, tibial cortical thickness and cortical area were significantly lower than control values, but no differences were seen in the radius. 49 Finally, Yin et al 50 have recently reported reduced trabecular bone density in the tibia and radius and lower cortical and trabecular thickness in young American-African or Hispanic men.…”
Section: Pathophysiology Of Bone Loss Associated With Hiv Infectionmentioning
confidence: 98%